2020
DOI: 10.1002/mds.27951
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neuropathological Features Associated With Loss of RAB39B

Abstract: AB S T R A C T : Background: Pathogenic variantsin the small GTPase Ras Analogue in Brain 39b (RAB39B) have been linked to the development of earlyonset parkinsonism. The study was aimed at delineating the clinical and neuropathological features associated with a previously reported pathogenic variant in RAB39B (c.503C>A p.T168K) and testing for dysregulation of RAB39B in idiopathic PD. Methods: Clinical details of a male individual hemizygous for the T168K variant were collected by systematic review of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…Specifically, the function(s) of RAB39B in cortical and hippocampal regions are likely to be associated with the development of cognitive impairment, whilst its function(s) in the SNpc could be linked to the development of parkinsonism. Consistent with the mouse data reported herein, we have recently demonstrated substantial steady-state levels of RAB39B in human cortex, hippocampus and substantia nigra [14]. These observations suggest the mouse represents an appropriate model for further studies to investigate the pathological mechanisms underlying parkinsonism and cognitive dysfunction in RAB39B-mediated disease.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, the function(s) of RAB39B in cortical and hippocampal regions are likely to be associated with the development of cognitive impairment, whilst its function(s) in the SNpc could be linked to the development of parkinsonism. Consistent with the mouse data reported herein, we have recently demonstrated substantial steady-state levels of RAB39B in human cortex, hippocampus and substantia nigra [14]. These observations suggest the mouse represents an appropriate model for further studies to investigate the pathological mechanisms underlying parkinsonism and cognitive dysfunction in RAB39B-mediated disease.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, we demonstrated that RAB39B is an abundant protein in dopaminergic neurons in the SNpc, the neuronal subtype selectively lost in PD. (14). These observations suggest the mouse represents an appropriate model for further studies to investigate the pathological mechanisms underlying parkinsonism and cognitive dysfunction in RAB39B-mediated disease.…”
Section: Discussionmentioning
confidence: 96%
“…A genetic analysis of the UTRs and the regulatory regions of RAB39B has not been reported previously; our identification of a novel 5 ′ variant, with in silico predictions supporting pathogenicity, warrants further investigation. Moreover, a recent study in a small cohort of individuals with idiopathic PD suggested that steady-state levels of RAB39B in brain tissue might be decreased (34). Therefore, further genetic and functional studies are required to determine the consequences of dysregulated RAB39B expression and test its potential role as a susceptibility gene associated with PD or parkinsonism more broadly.…”
Section: Discussionmentioning
confidence: 99%